2023
DOI: 10.1002/clc.24004
|View full text |Cite
|
Sign up to set email alerts
|

Mortality across the spectrum of hemoglobin level in patients undergoing surgical coronary revascularization

Abstract: Background Preoperative hemoglobin (Hb) level is a predictor of in‐hospital and midterm mortality in patients undergoing coronary artery bypass grafting surgery (CABG). However, the debate about the different hazards across Hb levels and sex differences in outcome occurrence is still on the table. Methods This is a registry‐based serial cross‐sectional study at Tehran Heart Center. Nonanemic patients who underwent CABG with complete follow‐up data were included. The Restricted Cubic Splines (RCS) in the Cox mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…The following may be the underlying mechanisms [ 40 ]: (1) reduction in tissue oxygen intake; (2) increased instability of the plaque; and (3) decreased nitric oxide secretion. Past studies have suggested anemia as an independent risk factor for adverse outcomes in elderly individuals [ 41 , 42 ]. Notably, our investigation also identified an intriguing interaction between cardio-cerebrovascular comorbidities and anemia concerning all-cause mortality.…”
Section: Discussionmentioning
confidence: 99%
“…The following may be the underlying mechanisms [ 40 ]: (1) reduction in tissue oxygen intake; (2) increased instability of the plaque; and (3) decreased nitric oxide secretion. Past studies have suggested anemia as an independent risk factor for adverse outcomes in elderly individuals [ 41 , 42 ]. Notably, our investigation also identified an intriguing interaction between cardio-cerebrovascular comorbidities and anemia concerning all-cause mortality.…”
Section: Discussionmentioning
confidence: 99%